Determinants of capital structure: Empirical evidence from Shariah compliant plantation firms in Malaysia / Mohamad Nizam Jaafar … [et al.] - Jaafar, Mohamad Nizam; Muhamat, Amirul Afif; Ahmad, Ismail; Syed Alwi, Sharifah Faigah (Universiti Teknologi Mara Selangor, 2017)
Capital structure choice is vital in corporate financial management due to its effect on both return and risk to investors. As such, the objective of this research is to analyse the capital structure of listed shariah compliant plantation companies in Bursa Malaysia. The factors that influence the level of debt in this research are profitability, tangibility and liquidity respectively. The research is conducted by observing financial data of 34 listed shariah compliant plantation firms in Malaysia from period 2006 to 2016. The study has used panel data and the regression analysis is based on ordinary least square (OLS). Capital structure is the dependaple variable referring to debt ratio of the companies, decomposed into total debts over total assets. The independent variables are profitability, liquidity and tangibility. Three theories of capital structure have guided this study i.e. the Trade-Off Theory, Asymmetric Information and the Pecking Order Theory. The study shows that profitability and tangibility have significant positive relationship capital structure. Nevertheless, liquidity does not have any significant relationship with the debt ratio. It is most likely that liquidity is not taken into account by listed plantation companies in Malaysia in making their capital structure decision. Since profitability and tangibility have significant relationship with the level of debt, the Theory of Capital Structure such as Trade Off Theory is applicable to plantation shariah compliant firms listed in Bursa Malaysia.